Expert System to Diagnose Extra Lung Tuberculosis Using Bayes Theorem: Expert System to Diagnose Extra Lung Tuberculosis Using Bayes Theorem - Fristi Ridandari; Agustinus Clinton Panjaitan (Institute of Computer Science (IOCS), 2019)
Tuberculosis is a common infectious disease, and in many cases is deadly. Tuberculosis usually attacks the lungs, but can also affect other body parts. Tuberculosis spreads through the air when someone with active TB infection coughs, sneezes, or spreads their saliva through the air. the limited medical staff in the puskesmas compared to the total population results in often delayed services to TB patients. This research focuses on making an expert system to diagnose tuberculosis using Bayes's Theorem which has been known that the method has been widely used to diagnose diseases in several cases